2022
DOI: 10.1002/gps.5828
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of process evaluations for psychosocial interventions designed to improve the wellbeing and quality of life of community‐dwelling people with dementia and their carers

Abstract: Background: Psychosocial interventions improve the wellbeing and quality of life of People Living with Dementia (PLWD) and their family carers; but due to their complexity it can be challenging to identify mechanisms of action. We reviewed process evaluations that have sought to elucidate how these interventions work, to inform their implementation. Method:We systematically reviewed process evaluations of studies evaluating psychosocial interventions for PLWD in their own home and/or their family carers.We rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(537 reference statements)
0
2
0
Order By: Relevance
“…Methodological strengths of this process evaluation are its theory-based design, and triangulated data sources (8,15). The recruited sample of people with dementia was balanced for gender, and the proportions from non-White ethnic groups, and who owned their home were broadly comparable to the older general population (16).…”
Section: Discussionmentioning
confidence: 99%
“…Methodological strengths of this process evaluation are its theory-based design, and triangulated data sources (8,15). The recruited sample of people with dementia was balanced for gender, and the proportions from non-White ethnic groups, and who owned their home were broadly comparable to the older general population (16).…”
Section: Discussionmentioning
confidence: 99%
“…There was strong evidence supporting the adaptation or modification of interventions as required based on individual client need in providing a person centred, flexible approach [ 31 , 32 , 34 , 36 , 37 , 42 , 46 , 52 , 55 , 56 , 58 , 60 62 , 69 , 72 ]. Wyman and colleagues in a recent review reported key implementation factors that influence the impact of interventions, including, interventions tailored to stage of dementia, flexibility of delivery, participants engagement and carer supported [ 77 ].…”
Section: Discussionmentioning
confidence: 99%